2011
DOI: 10.1074/jbc.m110.196832
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Enhances Carbachol-induced Protease Activation and Accelerates Ca2+ Waves in Isolated Rat Pancreatic Acini

Abstract: Alcohol abuse is a leading cause of pancreatitis, accounting for 30% of acute cases and 70 -90% of chronic cases, yet the mechanisms leading to alcohol-associated pancreatic injury are unclear. An early and critical feature of pancreatitis is the aberrant signaling of Ca 2؉ within the pancreatic acinar cell. An important conductor of this Ca 2؉ is the basolaterally localized, intracellular Ca 2؉ channel ryanodine receptor (RYR). In this study, we examined the effect of ethanol on mediating both pathologic intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Our findings that blockade of intracellular Ca 2ϩ reduced calcineurin activation are in general agreement with previous reports that sustained Ca 2ϩ signals are required to activate calcineurin (22,23 (12,25,46), Ca 2ϩ store depletion, and the subsequent opening of store operated Ca 2ϩ entry (SOCE) channels (47)(48)(49).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings that blockade of intracellular Ca 2ϩ reduced calcineurin activation are in general agreement with previous reports that sustained Ca 2ϩ signals are required to activate calcineurin (22,23 (12,25,46), Ca 2ϩ store depletion, and the subsequent opening of store operated Ca 2ϩ entry (SOCE) channels (47)(48)(49).…”
Section: Discussionsupporting
confidence: 92%
“…In vivo, administration of dantrolene blocked pancreatic injury when given before bile acid infusion, and it also ameliorated pancreatitis when given as therapy after bile infusion. In previous work, we and others have shown that basolateral Ca 2ϩ amplitude and Ca 2ϩ wave speed with supraphysiological secretagogue stimulation were dependent on the RyR (22,29,32,36,45). In our current work, we find that RyR inhibition reversed the pattern of the acinar cell Ca 2ϩ signals (in most acinar cells) induced by pathological concentrations of bile acids from a peak-plateau to that of Ca 2ϩ oscillations.…”
Section: Discussionmentioning
confidence: 82%
“…Exposing either experimental animals or isolated pancreatic acinar cells to EtOH sensitizes the cells to physiologic secretagogue stimulation (22)(23)(24)(25)(26) and deregulates normal agonist-in-duced Ca 2ϩ responses and zymogen activation (27,28). Specifically, it has been shown that after treatment of isolated pancreatic acinar cells either with EtOH or its non-oxidative metabolites, physiological concentrations of secretagogue induces sustained increases in [Ca 2ϩ ] cyto that are no longer limited to the apical pole but spread throughout the acinar cell (28,29).…”
mentioning
confidence: 99%
“…Specifically, it has been shown that after treatment of isolated pancreatic acinar cells either with EtOH or its non-oxidative metabolites, physiological concentrations of secretagogue induces sustained increases in [Ca 2ϩ ] cyto that are no longer limited to the apical pole but spread throughout the acinar cell (28,29). Associated with the prolonged aberrant Ca 2ϩ signal is an inhibition of apical zymogen secretion (30), impaired mitochondrial function (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation